Challenges at the Time of COVID-19: Opportunities and Innovations in Antivirals from Nature - Hensel, Andreas; Bauer, Rudolf; Heinrich, Michael; Spiegler, Verena; Kayser, Oliver; Hempel, Georg; Kraft, Karin (Planta Medica, 2020)
As viral infections are an increasing threat to human societies, the need for new therapeutic strategies is becoming even more obvious. As no vaccine is available for COVID-19, the development of directly acting antiviral agents and preventive strategies have to be considered. Nature provides a huge reservoir of anti-infectious compounds, from which we can deduce innovative ideas, therapies, and products. Anti-adhesive natural products interact with the receptor-mediated recognition and early interaction of viruses with the host cells, leading to a reduced internalisation of the virus and reduced infections (e.g., procyanidin-B-2-di-O-gallate against influenza and herpes virus). Lignans like podophyllotoxin and bicyclol show strong antiviral activities against different viruses, and essential oils can directly interact with viral membranes and reduce the hostʼs inflammatory responses (e.g., 1,8-cineol). Echinacea extracts stimulate the immune system, and bioavailable alkamides are key players by interacting with immunomodulating cannabinoid receptors. COVID-19 and SARS-CoV-2 infections have, in part, successfully been treated in China by preparations from traditional Chinese medicine and, while it is too early to draw conclusions, some promising data are available. There is huge potential, but intensified research is needed to develop evidence-based medicines with a clearly defined chemical profile. Intensified research and development, and therefore funding, are needed for exploiting natureʼs reservoir against viral infections. Combined action for basic research, chemistry, pharmacognosy, virology, and clinical studies, but also supply chain, sustainable sourcing, and economic aspects have to be considered. This review calls for intensified innovative science on natural products for the patients and for a healthier world!
Keywords: COVID; Coronaviridae; Echinacea; Asteraceae; virus; tannins; lignans; anti-adhesion; immune system; phytotherapy